The Onset of Whole-Body Regeneration in Botryllus schlosseri: Morphological and Molecular Characterization - Ricci, Lorenzo; Salmon, Bastien; Olivier, Caroline; Andreoni-Pham, Rita; Chaurasia, Ankita; Alié, Alexandre; Tiozzo, Stefano (Frontiers in Cell and Developmental Biology, 2022)
Colonial tunicates are the only chordates that regularly regenerate a fully functional whole body as part of their asexual life cycle, starting from specific epithelia and/or mesenchymal cells. In addition, in some species, whole-body regeneration (WBR) can also be triggered by extensive injuries, which deplete most of their tissues and organs and leave behind only small fragments of their body. In this manuscript, we characterized the onset of WBR in Botryllus schlosseri, one colonial tunicate long used as a laboratory model. We first analyzed the transcriptomic response to a WBR-triggering injury. Then, through morphological characterization, in vivo observations via time-lapse, vital dyes, and cell transplant assays, we started to reconstruct the dynamics of the cells triggering regeneration, highlighting an interplay between mesenchymal and epithelial cells. The dynamics described here suggest that WBR in B. schlosseri is initiated by extravascular tissue fragments derived from the injured individuals rather than particular populations of blood-borne cells, as has been described in closely related species. The morphological and molecular datasets here reported provide the background for future mechanistic studies of the WBR ontogenesis in B. schlosseri and allow to compare it with other regenerative processes occurring in other tunicate species and possibly independently evolved.